Analisis Pelaksanaan Pembinaan Industri Kecil Oleh Dinas Perindustrian Dan Perdagangan Di Kecamatan Tampan Kota Pekanbaru - Masrianto Masrianto; Nurmasari Nurmasari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
The implementation of the small industry development and development program can be successful and efficient if the small industry development program can provide great benefits to small industries, especially helping small industries solve their problems (such as: capital, use of technology, etc.) globalization development. The purpose of this study is to identify and analyze the implementation of small industry development by the Department of Industry and Trade in the handsome district of Pekanbaru City, and to determine the inhibiting factors in the implementation of small industry development. The method used in this study is a quantitative method. Questionnaire Observation, Interview and Documentation are techniques used to collect data. The results of this study are from the indicators of guidance, supervision, supervision, and information, it can be concluded that the implementation of small industry development by the Industry and Trade Office of Pekanbaru City (Study in the handsome district of Pekanbaru City) is "Good Enough" with a percentage of 34%-66%. This means that the guidance provided by the Department of Guidance, Guidance, and Training for small industry players in the city of Pekanbaru, especially in the handsome district of Pekanbaru City, has been running, but is not optimal because the coaching activity is carried out only once a year or it can be said not to. Routinely.